2020
DOI: 10.3390/polym12051021
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning of Cellulose Nanocrystal-Reinforced Polyurethane Fibrous Mats

Abstract: We report the electrospinning of mechanically-tunable, cellulose nanocrystal (CNC)-reinforced polyurethanes (PUs). Using high-aspect ratio CNCs from tunicates, the stiffness and strength of electrospun PU/CNC mats are shown to generally increase. Furthermore, by tuning the electrospinning conditions, fibrous PU/CNC mats were created with either aligned or non-aligned fibers, as confirmed by scanning electron microscopy. PU/CNC mats having fibers aligned in the strain direction were stiffer and stronger compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Melt processing of CNCs with various polymeric matrices was previously achieved with cellulose acetate butyrate, 27 poly(oxyethylene), 35 polyamide, 36 polycarbonate, 37 polyethylene, 12,38,39 poly(lactic acid), 26,28,40−42 polystyrene, 43 poly(vinyl acetate), 44 and different PUs. [16][17][18]45,46 However, the melt spinning of CNC/ polymer nanocomposite fibers has been challenging due to the reduced elasticity of the materials upon CNC addition and their low thermal stability. CNC production involves the partial degradation of cellulose by acid hydrolysis, typically employing sulfuric acid.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melt processing of CNCs with various polymeric matrices was previously achieved with cellulose acetate butyrate, 27 poly(oxyethylene), 35 polyamide, 36 polycarbonate, 37 polyethylene, 12,38,39 poly(lactic acid), 26,28,40−42 polystyrene, 43 poly(vinyl acetate), 44 and different PUs. [16][17][18]45,46 However, the melt spinning of CNC/ polymer nanocomposite fibers has been challenging due to the reduced elasticity of the materials upon CNC addition and their low thermal stability. CNC production involves the partial degradation of cellulose by acid hydrolysis, typically employing sulfuric acid.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Efficient mechanical reinforcement of polymers through the addition of CNCs can be achieved by carefully optimizing the processing of the composite material and the interfacial interactions between CNCs and the polymer matrix. , Alternatively, specific processing protocols or dispersing agents can be used in the composite fabrication. Polyurethane (PU) matrices have been shown to be particularly suitable for CNC reinforcement, as their urethane and ether functional groups can interact with the hydroxy groups on the CNC surface, thereby enabling tailored interfacial interactions between the CNCs and the PU matrix. Previous studies have shown that the extent of reinforcement of CNC/PU nanocomposite films follows the predictions of a percolation model, suggesting that good dispersion is possible .…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement of properties of electrospun nonwovens by the introduction of CNT to electrospun polymer solutions was reported for different polymers, including poly(ethylene terephthalate), poly(vinylpyrrolidone), polyacrylonitrile/poly(vinyl chloride) blend, polyamide 6, and polylactide (PLA), among others [ 3 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Modification of electrospun nonwovens can be also achieved by incorporating other nanoparticles, for example, graphene oxide [ 14 ], cellulose nanocrystals [ 22 ], or hydroxyapatite nanoparticles [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…A few previous studies have reported the electrospinning of polymers containing CNCs. For example, Redondo et al [ 61 ] incorporated CNCs into polyurethane (PU) fibers and reported an improvement in the mechanical properties of the nanocomposite fiber mats. In another work, PVA mats prepared by electrospinning were mixed with CNC solutions to form aerogels that were subsequently hot-pressed to form nanocomposites.…”
Section: Introductionmentioning
confidence: 99%